EFFECT OF NIPPING AT VARIOUS STAGES ON YIELD AND YIELD COMPONENTS OF CHICKPEA (Cicer aritinum L.) - Khan, Hamayun; Latif, Abdul; Mahmood, Sultan; Khan, Muhammad Shah Sawar (Journal of Research (Science), 2006)
Nipping the young tender shoots during the early and middle growth phases of chickpea is a normal practice in Southern districts of N.W.F.P. To check the nipping effects on yield and yield components, a three year study (1995-1998) was conducted at ARS, Ahmad Wala, Karak. Eight nippings with 20 days interval were done following the RCB design during the growing seasons. Data collected for each trait during the years were averaged and statistically analyzed. The analyzed data revealed that traits like number of productive branches per plant, number of pods per plant, 100 seeds weight and yield (kg ha-1) varied significantly due to nippings. However, number of seeds per pod remained non-significant. Plants nipped in the last week of December to the end of January showed enhancement in productive branches, pods and grain yield while reduction in 100 seeds weight. A very strong positive correlation (0.946) was observed between number of pods per plant and yield which is reported to be 0.04 in the ordinary situations. Quantitative increase up to 53 % in yield (kg ha-1) was observed in the plants when nipped on December 26, 1997. Based on the findings of this study it is recommended that nipping be done in the chickpea crop from the last week of December to the end of January to have increased yield and extra feed to the cattle.